Use of Traditional Birth Practices by Chinese Women in the United States. Issue 3 (May 2017) - Saito, Maki; Lyndon, Audrey
Abstract: Purpose: The purpose of our study was to explore how foreign-born Chinese women living in California engage in various traditional and American birth practices. Study Design and Methods: A descriptive qualitative study was conducted using a grounded theory approach. Chinese women from Mainland China, Hong Kong, and Taiwan who had childbirth experiences in the United States were purposively sampled. Semistructured interviews were conducted with 13 women, with follow-up interviews with 5 women. Interview data were analyzed using grounded theory according to the method of Strauss and Corbin. Results: There are many traditional practices for pregnancy and childbirth. Women investigated the traditions through various means, and built their own perspective on each tradition by integrating an evaluation of the Chinese perspective and an evaluation of the American perspective. Women considered several factors in the process of evaluating the Chinese and American perspectives to reach their own integrated perspective on each tradition. These factors included whether or not the tradition made sense to them, how the traditional practice affected their comfort, nature of available options, attitudes of female elders, previous experiences of their peers and themselves, and outcomes of temporary trials of traditional or nontraditional practices. Clinical Implications: Healthcare providers should respect women's diverse perspectives on traditional practices and encourage flexible arrangements. Including the elder generation in health education may be useful in helping women manage conflicts and to support their decisions. Abstract : With globalization, many women are giving birth in countries other than where they were born. This study explores use of traditional birth practices by Chinese women in the United States. Chinese women giving birth in the United States respect traditional childbirth practices, while building their own views of each tradition by integrating an evaluation of Chinese and American perspectives.